FAKTOR PENGUAT PADA PENINGKATAN KINERJA KARYAWAN PT. GADING MURNI SURABAYA - Iwang Suwangsih, Iwang Suwangsih (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2019)
Abstract The purpose of this study is to determine which factors as an amplifier to improve the performance of employees of PT. Gading Murni Surabaya, between the leadership style and compensation received by employees. This study uses a survey approach by collecting data using a questionnaire of 50 respondents then analyzed using quantitative methods. The regession equation is Y = 8.009 + 0,223 X1 + 0,240 X2. The results of this study concluded that the leadership style and compensation variables had a corrected item total correlation value exceeding r table = 0.284 and the reliability test of the leadership style variable, and the alpha cronbach's compensation results exceeded 0.060, which means that the variable was valid and reliable. Leadership and compensation styles also simultaneously have a significant effect on employee performance. And the independent variable that has the largest beta coefficient is the compensation variable (X2) with a beta coefficient of 0.240.